2022
DOI: 10.3390/su15010586
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Self-Efficacy on Fitness Use Innovativeness and Usage Pattern

Abstract: Marketing researchers agree that use innovativeness leads to variety-seeking behavior in service usage in service contexts. As fitness consumers are high-frequency users, user behavior can be enriched by exploring the moderating effect of self-efficacy. This study explores the moderating effect of self-efficacy on the relationship between fitness use innovativeness and usage patterns (usage variety and usage frequency), and investigates their mediation effects on satisfaction and revisit intention. A sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Higher self-efficacy in using diet programs fosters confidence in adhering to recommendations, thereby influencing app adoption intention. Satjawathee et al (2022) also emphasize that individuals with high self-efficacy feel competent in managing risks, such as privacy concerns, enhancing their intention to use apps. Conversely, individuals with low self-efficacy may perceive risks as formidable obstacles, reducing their inclination to use apps.…”
Section: Self-efficacymentioning
confidence: 99%
“…Higher self-efficacy in using diet programs fosters confidence in adhering to recommendations, thereby influencing app adoption intention. Satjawathee et al (2022) also emphasize that individuals with high self-efficacy feel competent in managing risks, such as privacy concerns, enhancing their intention to use apps. Conversely, individuals with low self-efficacy may perceive risks as formidable obstacles, reducing their inclination to use apps.…”
Section: Self-efficacymentioning
confidence: 99%
“…Son and Han [ 34 ] confirmed that high innovative use and frequent use of technology-based products tends to produce higher retention levels, because new ways of using these products have been learned. Satjawathee et al [ 35 ] also found that a higher level of usage variety and frequency lead to a higher satisfaction and revisit intention on fitness services.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…In a remote setting, service providers offer a variety of contract methods, which can help to increase trust. Consumer self-efficacy in managing these interactions becomes important, including cognitive diversity that aids in research generalization (Choi, 2019;Chung & Lin, 2023;Hong, Pavlou, Shi, & Wang, 2017;Satjawathee, Ma, Shu, & Chang, 2022). This study considers social trust and self-efficacy as key elements encouraging users to use sharing economy platforms.…”
mentioning
confidence: 99%